Associative plural as indexical category. (September 2020) - Daniel, Michael
Abstract: The Animacy Hierarchy was introduced as a cross-grammatical factor which governs, in different languages, widespread splits of nominal categories, including case or number marking. Among othser phenomena, the Animacy Hierarchy has been invoked to describe the lexical distribution of associative plurals. In this paper I argue that associative plurals as an interpretation of nominal plurality is not licensed by the high position the respective noun holds on the Animacy Hierarchy but is a combined effect of coercion by the unique reference inherent to proper names and associative links easily recoverable for human referents. Interpretation of associative plurals relies upon activation of set relations its referent holds to other entities in the speech act situation. Associative plural is argued to be an indexical rather than a functional semantic category.∗ Highlights: APL reading is coerced by unique reference of the noun and interpreted via activating associative links. APL are observed as lexicalized plurals in inanimate nouns. APL are indexical in a way similar to, but different from, plural personal pronouns. APL cannot be explained as the effect of the Animacy Hierarchy.